Development and usability testing of a data visualisation platform for an African trauma data registry - Griffith, Bridget Catherine Hamilton (Division of Emergency Medicine, 2019)
Introduction Trauma is a significant contribution to the global burden of mortality and disease, especially in sub-Saharan Africa. The methods for tracking, recording, and analysing the incidence and causes of trauma are underdeveloped. To address this, The African Federation for Emergency Medicine (AFEM) developed a trauma form and Trauma Data Registry to collect trauma data in multiple sites in sub-Saharan Africa. We undertook a study to create, and assess the usability and functionality of, a trauma data visualisation platform for use in conjunction with the Trauma Data Registry. Methods We created a web-based trauma data visualisation platform for use with the AFEM Trauma Data Registry. This study involves a usability assessment of the AFEM Trauma Data Visualisation Platform to determine the specific website features and analytical needs of African trauma research facilities. This was done by surveying individuals from healthcare facilities that are currently using the AFEM Trauma Form. Two types of questionnaires were administered: Questionnaire I gathered information on the study population and their expectations for the platform, and Questionnaire II assessed the usability of the platform after it was introduced. Surveys took place in person and online, with the last group of questionnaires being administered on-site at the healthcare facility. Data were captured via Survey Monkey online and paper survey. The results were entered into Excel and analysed using descriptive statistics using Stata Version 14. Results A total of 45 healthcare practitioners from eight countries participated in the background survey. The greatest proportion were trained in Tanzania (14, 31.1%) and Ethiopia (14, 31.1%). The mean age of participants was 32.6 (SD=6.6). The mean number of years reported for working at their current facility is 3.7 (SD=3.5). The greatest number of participants in the survey were physicians (22, 48.9%) and specialists (11, 24.4%). Over half (53.3%, n=24) selected that they had moderate experience with data analysis, and the majority reported that they had less than three publications. A total of 34 HCPs participated in the usability study. The mean scores for the usability questionnaire portion were high, with all of the scores being above 6. Major positive themes of the participant comments included easy to use and time saving, major negative themes included feasibility concerns, and comments specific variable to add were common. Discussion There is a lot of heterogeneity in the data analysis and technology experience of participants. The participants were overall satisfied with the Trauma Data Platform. Participants’ comments and suggestions on elements to add indicate that there is still work to be done to design a Trauma Data Platform that is suitable for this setting. Conclusions Overall satisfaction with the Trauma Data Platform was high, and the user comments and suggestions will be incorporated into future versions of the platform. This research highlights the importance of considering the feasibility of health technology in its introduction.